73‐4: Distinguished Paper: Image Formation Modeling and Analysis of Near‐Eye Light Field Displays. Issue 1 (29th May 2019) - Qin, Zong; Chou, Ping-Yen; Chen, Yu-Ting; Wu, Jui-Yi; Lin, Ting-Ru; Lin, Ting-Hsuan; Balram, Nikhil; Huang, Yi-Pai
Abstract : The image formation of microlens array‐based near‐eye light field displays is modeled with near‐perfect accuracy by incorporating diffraction, ray aberration, defocusing, and pixel sampling. Based on this model, algorithms and hardware parameters are suggested for resolution optimization, and the resolution variations with FOV and image depth are analyzed.